Perceived Benefits and Understanding of Artificial Intelligence (AI) Among Vocational University Students - Nabila, Salma Reza; Oktavianda, Melti; Fitriani, Nurul (Universitas Muhammadiyah Pontianak, 2024)
This study explores the understanding, perceptions, and expectations of vocational university students regarding Artificial Intelligence (AI), with a focus on its potential impact on education. As AI becomes increasingly integrated into various sectors, assessing students' preparedness for an AI-driven workforce is crucial. Using a mixed-methods approach, the research surveyed students from different disciplines, examining their knowledge of AI, its applications in education, and their attitudes toward its future development. The findings reveal that while students recognize AI's potential to enhance learning and efficiency, their awareness of its ethical implications and broader societal impacts remains limited. Most students expressed a strong interest in further exploring AI's evolving applications. The study suggests that vocational education AI literacy programs should encompass technical skills and ethical considerations to better prepare students for the challenges of an AI-powered future. This research underscores the importance of fostering a balanced understanding of AI, combining technological proficiency with ethical awareness to ensure responsible engagement with AI in the future workforce.